Adaptive fuzzy sliding mode control of a washing machine oscillating system - Tamyaman, Can. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2005., 2005)
To prevent any mechanical damage, washing machines distribute the load (the laundry)before performing any spins. After some distributive motor movements, there may still besome load that does not lay homogenously on the surface of the tumble. This load may cause undesired oscillations of the system. In cases when the load is not distributedhomogenously, the washing machine senses this unbalanced distribution if it is over athreshold value and reduces the spin speed or does not perform the final spin in thewashing profile. Because the machine is allowed to perform the final spin if the unbalanced distribution measurements are under a certain limit; some undesired oscillations andovershoots in the displacement of the oscillating system of the washing machine is likely totake place. This shortens the mechanical life of the machine. Furthermore, any undesiredmovements of the machine may pose a danger in a household. For these reasons the risk of machine displacement should be calculated and tested on every washing machine at thedesign phase. The machines are either produced with a calculated risk of displacement, orthe spin profile is modified to reduce the risk according to the results of the tests at designlevel. In this thesis, the control of a washing machine suspension system is achieved byusing adaptive fuzzy sliding mode control methods. The design and implementations are carried out in MATLAB Simulink environment. In the thesis, first, the methods that aregoing to be used and their advantages are given. Then, the unbalanced distribution of loadand its effects on washing machines are explained. Finally, the behavior of the proposed suspension system is examined in Simulink environment.
Keywords: Fuzzy systems.; Fuzzy logic.